Street Codes and Adolescent Violent Victimization at School: Unpacking a Complex Relationship - O, SooHyun (Crime & delinquency, 2021)
This study examines the effects of adherence to street codes on school-based violent victimization. In doing so, it separates street values into two distinct orientations: (1) retaliatory norms, and (2) general toughness norms. We analyze survey data from students across four waves of the Rural Substance Abuse and Violence Project using two-level mixed effects Poisson regression. The model specifies random intercepts across individuals to address possible endogeneity of the repeated measurements per respondent. Further, consistent with a fixed-effects approach, we control for differences across the schools in which students were nested. Findings reveal that adherence to retaliatory norms is negatively related to the frequency of serious violent victimization. In contrast, general toughness norms are positively related to serious violent victimization.